Therapeutic Plasma Exchange Protects Patients with Sepsis-Associated Disseminated Intravascular Coagulation by Improving Endothelial Function - Junting Weng MD (SAGE Publishing, 2021)
The mortality rate of sepsis-associated disseminated intravascular coagulation (DIC) is high. This study aimed to explore the efficacy of therapeutic plasma exchange (TPE) in sepsis-associated DIC patients by improving endothelial function. A total of 112 sepsis-associated DIC patients were randomly divided into the TPE group (n = 40), the heparin (HP) group (n = 36), and the SHAM group (n = 36). The SHAM group received conventional treatment; the HP group was treated with HP based on conventional treatment; and the TPE group received conventional treatment plus TPE. The differences in thromboelastogram (TEG), platelet (PLT), coagulation function, and the endothelial cell (EC) injury biomarkers at 6 h, 24 h, 48 h, 72 h, and 7 days after TPE were compared among the three groups, and the three groups were compared in terms of Acute Physiology and Chronic Health Evaluation II (APACHE II) score, Sepsis-Related Organ Failure Assessment (SOFA) score, the length of intensive care unit (ICU) hospitalization, 28-day mortality rate, 28-day cumulative survival rate, the incidence of bleeding events, the incidence of acute kidney injury (AKI), and acute respiratory distress syndrome (ARDS). The efficacy of TPE is superior to the HP in increasing PLT, improving coagulation function, increasing the 28-day cumulative survival rate, and reducing the length of ICU hospitalization, 28-day mortality, and the incidence of bleeding events, AKI, and ARDS with statistically significant differences ( P   <  .05). Moreover, the effect of TPE outperforms HP on the EC injury biomarkers with statistically significant differences ( P   <  .05). Our results suggest that TPE may be more effective than HP in the treatment of patients with sepsis-associated DIC. The possible mechanism is via improving endothelial function.